Molecular Characterization of SehB, a Type II Antitoxin of Salmonella enterica Serotype Typhimurium: Amino Acid Residues Involved in DNA-Binding, Homodimerization, Toxin Interaction, and Virulence - Chimal-Cázares, Fernando; Hernández-Martínez, Gabriela; Pacheco, Sabino; Ares, Miguel A.; Soria-Bustos, Jorge; Sánchez-Gutiérrez, Manuel; Izquierdo-Vega, Jeannett A.; Ibarra, Jose Antonio; González-y-Merchand, Jorge A.; Gorvel, Jean-Pierre; Méresse, Stéphane; De la Cruz, Miguel A. (Frontiers in Microbiology, 2020)
Salmonella enterica serotype Typhimurium is a bacterium that causes gastroenteritis and diarrhea in humans. The genome of S. Typhimurium codes for diverse virulence factors, among which are the toxin-antitoxin (TA) systems. SehAB is a type II TA, where SehA is the toxin and SehB is the antitoxin. It was previously reported that the absence of the SehB antitoxin affects the growth of S. Typhimurium. In addition, the SehB antitoxin can interact directly with the SehA toxin neutralizing its toxic effect as well as repressing its own expression. We identified conserved residues on SehB homologous proteins. Point mutations were introduced at both N- and C-terminal of SehB antitoxin to analyze the effect of these changes on its transcription repressor function, on its ability to form homodimers and on the virulence of S. Typhimurium. All changes in amino acid residues at both the N- and C-terminal affected the repressor function of SehB antitoxin and they were required for DNA-binding activity. Mutations in the amino acid residues at the N-terminal showed a lower capacity for homodimer formation of the SehB protein. However, none of the SehB point mutants were affected in the interaction with the SehA toxin. In terms of virulence, the eight single-amino acid mutations were attenuated for virulence in the mouse model. In agreement with our results, the eight amino acid residues of SehB antitoxin were required for its repressor activity, affecting both homodimerization and DNA-binding activity, supporting the notion that both activities of SehB antitoxin are required to confer virulence to Salmonella enterica.